Updating the uniform accounting system in Iraq for installment sales transactions framework - عبد الله سلمان حسين; مجيد محمد زهير (Journal of Economics and Administrative Sciences, 2018)
Due to the intensity of competition between economic units that run the trade in durable goods had to pay a lot of these companies to follow the new selling methods aimed at attracting customers to be able to increase its sales and thereby increase their profits , these methods are installment sales, which had been in great demand by the customers with limited income, who provides them with the possibility of possession and use of such goods and to postpone the full amount of the payment to the seller, This transaction sales have grown even became installment sales system at the present time of the common types of sales transactions and deployed a lot in our environment and in many sectors of the market, and in some cases made total reliance by the economic units in the discharge of their production, to provide this system of advantages of the seller and the buyer, Due to the large volume of transactions handled installment sale was necessary to strengthen the Iraqi unified accounting system to add rules to measure special accounts that can be applied uniformly in the Iraqi economic institutions , that working an installment sales system. to makes this system better able to provide appropriate accounting information and with confidence when its users, because the accounting system applied in these units does not cover all types of sales, such as installment sales and does not help to build a management information systems for the production of standardized data, to the levels of the economy, to be in line with the new economic environment of the Iraqi units.